Lateral Approach to Thyroid Surgery: An Alternative Open Thyroidectomy Technique - Bhandari, Ramesh; Aryal, Bivek; Sapkota, Anika; Kandel, Damodar; Sharma, Sona (Journal of National Heart and Lung Society Nepal, 2023)
Background: Thyroidectomy is one of the common surgical procedures for thyroid related various pathology. Midline approach is the classical and common in which thyroid gland is approached after splitting the strap muscles in midline. The objective of this research is to elaborate the surgical technique of lateral thyroid approach for hemi-thyroidectomy, also to measure the efficacy in preserving the important anatomical structures and to assess the complications. Materials: A cross-sectional study was conducted in the department of ENT-Head and Neck Surgery of Bharatpur Hospital, Chitwan, Nepal during January 2019 to March 2021. Benign thyroid diseases that required hemi-thyroidectomy were included in this study. Surgical technique was discussed with special focus for access of superior pedicle and preservation of important anatomical structures. Results: Among 36 cases most of those 16(44.4%) were operated after 1 year of disease occurrence. Not a single case was undergone strap muscle cutting or sacrifice of superior belly of omohyoid muscle. Recurrent laryngeal nerve was found in 94.4% (33 cases). External branch of superior laryngeal nerve (EBSLN) was in 91.7 %( 33) cases. Superior parathyroid glands were found in majority of the cases but not found in 8.3 %( 3). Inferior parathyroid glands were found in all cases. Post-operative drainage was 38 ml(mean). Conclusion: Vital structures were preserved in more than 90% cases and major complication occurred in none of the cases. We conclude that this approach is good, safe and comfortable to the surgeon.